Development and Validation of the Healthy Lifestyles Knowledge Questionnaire for Elderly at Risk of Heart Disease - Hardyanti Pratiwi; Ali Khomsan; Sri Anna Marliyati; Mira Dewi (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2026)
Introduction: Coronary heart disease (CHD) is a leading cause of mortality among the elderly. Promoting healthy lifestyles through balanced diets and regular physical activity is essential for prevention programs. However, the availability of standardized and validated instruments to measure knowledge of healthy lifestyles among elderly individuals is still limited, particularly in Indonesia. This study aimed to develop and validate a knowledge questionnaire focusing on diet and physical activity for elderly individuals at risk of CVD. Methods: A mixed-method validation was conducted, involving qualitative and quantitative approaches. First, content validity was assessed by experts in community nutrition, clinical nutrition, and sport nutrition (n = 8) using the Content Validity Index (CVI) and multi-rates Kappa statistics. Second, face validity was tested with elderly participants (n = 10) to ensure clarity and comprehension. Finally, item validity and reliability testing were examined with elderly participants (n = 30) using the Pearson correlation test between item-total score and Cronbach’s Alpha to determine internal consistency. Results: The I-CVI values for all items ranged from 0,75 to 1,00, and Kappa statistics from 0,72 to 1,00, indicating good to excellent agreement among experts. Face validation confirmed that most items were relevant and understandable, with brief wording adjustments required for clarity. The Cronbach’s alpha of 0,742 reflected good internal consistency. Overall, the validation process demonstrated that 19 of 28 items met the statistical criteria. Conclusion: The healthy lifestyle knowledge questionnaire demonstrated strong validity and reliability in assessing knowledge among elderly individuals at risk of CHD. This instrument is practical and applicable for supporting health promotion and prevention programs focusing on diet and physical activity.